Evaluation of Cellular and Molecular Mechanism of Anti-Asthmatic Effects of A Traditional Herbal Drug In Rats - Verma, Pankaj; Gulati, Kavita; Ray, Arunabha (Asian Journal of Pharmaceutical Research and Development, 2021)
The present study was performed to ascertain the therapeutic effects/aspects of Lychnis coronaria in ovalbumin (OVA) induced model of bronchial asthma in rats. Wistar rats were immunized with ovalbumin adsorbed on toaluminium hydroxide on day 0 followed by challenge with OVA on day 14 to experimentally induce/simulate bronchial asthma. Lychnis coronaria (1.5 mg/kg, 3 mg/kg and 6 mg/kg) was administered (orally) daily for 14 days and its effects on airway hyper responsiveness to spasmogen and airway inflammation were assessed. Enhanced pause (p-enh), a marker of airway hyper responsiveness, was measured in response to different doses of inhaled methacholine using whole body plethysmography, following which rats were anaesthetized and blood and bronchoalveolar lavage fluid (BALF) were collected and analyzed for OVA specific IgE, pro-inflammatory cytokine (TNF-α) and the Th-2 cytokine (IL-4). Results showed that OVA sensitization and challenge rats increased enhanced pause (P-enh) in response to different doses of methacholine as measured by whole body plethysmography. Assay of blood and BALF showed increased IgE, TNF-αand IL-4 levels as well as in OVA immunized + challenged rats compared to that of normal control rats thus validating the experimental model. Administration of Lychnis coronariafor 14 days induced dose-dependent reductions in p-enh values, as well as levels of OVA specific IgE, TNF-α and IL-4 as compared to that in the vehicle treated Disease control group. The result with prednisolone (10 mg/kg, orally) were comparable with Lychnis coronaria on all the parameters tested. The results showed anti-asthmatic effects of Lychnis coronaria via reducing bronchial hyper responsiveness as well as cellular and molecular markers of airway inflammation and immunity and thus, validating the therapeutic benefits of this Indian traditional medicinal plant for bronchial asthma